2010
DOI: 10.1177/0091270009359524
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Related Reduction in Bupropion Plasma Concentrations by Ritonavir

Abstract: The effect of repeat oral doses of ritonavir, at high (600 mg twice daily) and low (100 mg twice daily) doses, on the pharmacokinetics of a single dose of bupropion was evaluated in healthy volunteers. Subjects received a single dose of 150 mg of bupropion on day 1 and twice-daily ritonavir from day 8 through day 30. Ritonavir was up-titrated from 300 mg twice daily to 600 mg twice daily in the high-dose ritonavir study, whereas subjects remained on 100 mg twice-daily ritonavir in low-dose ritonavir study. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 17 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…increased 4-OH BUP Cl form (2.1-fold) and decreased BUP AUC 33% . RTV has been shown to cause a dose-dependent decrease in BUP AUC (66 and 22% for 600 and 100 mg b.i.d., respectively) (Park et al, 2010). The reason we did not observe a statistically significant decrease in BUP AUC is unclear.…”
Section: Discussionmentioning
confidence: 62%
“…increased 4-OH BUP Cl form (2.1-fold) and decreased BUP AUC 33% . RTV has been shown to cause a dose-dependent decrease in BUP AUC (66 and 22% for 600 and 100 mg b.i.d., respectively) (Park et al, 2010). The reason we did not observe a statistically significant decrease in BUP AUC is unclear.…”
Section: Discussionmentioning
confidence: 62%
“…57 Subsequent research has demonstrated that the pharmacokinetic clearance of bupropion is pronounced at exposure to high doses of ritonavir (600 mg twice daily), and substantially less so at lower doses, possibly requiring adjustments of bupropion dose (100 mg twice daily). 58 Further, the protease inhibitor combination of lopinavir and ritonavir (400/100 mg) was found to decrease bupropion maximum plasma concentration by 57% with similar reductions in hydroxybupropion concentrations among healthy volunteers. 59 Similarly, there is evidence that efavirenz can result in decreased bupropion plasma concentrations; however, the clinical implications remain unclear.…”
Section: Medication Treatmentsmentioning
confidence: 80%
“…Pharmacokinetic data are limited with respect to interactions with antiretrovirals; however, ritonavir and other boosted protease inhibitors have been shown to reduce the area under the curve for bupropion and sertraline by up to 50%-60% through induction of CYP2B6. [59][60][61] The boosted protease inhibitors fosamprenavir and darunavir have also been shown, in studies of healthy volunteers, to reduce the area under the curve for paroxetine by about 40%-60%; however, the mechanism for this interaction is unclear, as paroxetine is primarily a substrate of CYP2D6. 61,62 Serotonin syndrome was reported in a case series of patients receiving fluoxetine (a CYP2D6 substrate) in conjunction with high-dose (200-600 mg twice daily) ritonavir-based combination antiretroviral therapy.…”
Section: Metabolism: Other Cyp450 Isoenzymesmentioning
confidence: 99%